Choices strategy to maintain security of the transportation system - Гончаренко, А.В. (Proceedings of National Aviation University (archive), 2009)
Variants of a strategy choosing for a transport system functioning safety support is considered. Mathematical modelling by restriction indexes criteria of reliability, efficiency, and prevention measures costs is conducted. Attention is paid to the influence of unexpected loses due to crash events. Achieved results of applicable researches. Plotted appropriate diagrams.